2021
DOI: 10.1017/s1355617721000825
|View full text |Cite
|
Sign up to set email alerts
|

Aprosodia Subsequent to Right Hemisphere Brain Damage: A Systematic Review and Meta-Analysis

Abstract: Objective: To identify which aspects of prosody are negatively affected subsequent to right hemisphere brain damage (RHD) and to evaluate the methodological quality of the constituent studies. Method: Twenty-one electronic databases were searched to identify articles from 1970 to February 2020 by entering keywords. Eligibility criteria for articles included a focus on adults with acquired RHD, prosody as the primary research topic, and publication in a peer-reviewed journal. A quality ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 94 publications
1
15
0
Order By: Relevance
“…Lexical use in this instance demonstrates the use of ambiguous pronouns or referents after RHD (Balaban et al., 2016) as in the statement, ‘so they had to call the fire department to come with the ladder so they could get the daddy out of the tree ’. This communicative behaviour is consistent with recent work indicating that adults with RHD are less successful at resolving pronoun ambiguities during narrative discourse production (Stockbridge et al., 2021). It is also interesting that the utterances were frequently connected using the conjunction and , and contained few predicates, both of which are also consistent with prior work (conjunctions: Cherney, 1990; Sherratt & Penn, 1990; predicates: Davis et al., 1997).…”
Section: Rationale For the Label Apragmatismsupporting
confidence: 91%
“…Lexical use in this instance demonstrates the use of ambiguous pronouns or referents after RHD (Balaban et al., 2016) as in the statement, ‘so they had to call the fire department to come with the ladder so they could get the daddy out of the tree ’. This communicative behaviour is consistent with recent work indicating that adults with RHD are less successful at resolving pronoun ambiguities during narrative discourse production (Stockbridge et al., 2021). It is also interesting that the utterances were frequently connected using the conjunction and , and contained few predicates, both of which are also consistent with prior work (conjunctions: Cherney, 1990; Sherratt & Penn, 1990; predicates: Davis et al., 1997).…”
Section: Rationale For the Label Apragmatismsupporting
confidence: 91%
“…Nevertheless, RIFG showed a coactivation pattern, somewhat similar to LIFG, within left frontal (IFG, MFG, precentral gyrus, medial frontal regions), insular, parietal (IPL) and temporal (MTG, fusiform gyrus) cortices, as well as subcortical regions (thalamus). This implies that the right hemisphere, particularly RIFG, takes part not only in contextual, holistic and prosodic aspects of language processing as commonly argued in the literature (Dara et al, 2014;George et al, 1996;Lundgren & Brownell, 2016;Parola et al, 2016;Patel et al, 2018;Stockbridge et al, 2021;Xu et al, 2005), but also in lower-level semantic, phonological, syntactic and speech-related processes in conjunction with the left hemisphere. However, given that the behavioral analysis did not reveal any functional specificity for language subdomains within RIFG ROIs, that a disproportionately lower number of language-related studies were identified for RIFG ROIs than LIFG ROIs, and that both LIFG and RIFG ROIs coactivated mostly with left-hemispheric regions, the role of the right hemisphere in language processing seems to be rather limited.…”
Section: Coactivation Patterns Of Right-hemispheric Roismentioning
confidence: 62%
“…Cardillo, McQuire, & Chatterjee, 2018, processing contextual and coherent meaning particularly in discourse (Vigneau et al, 2011;Xu, Kemeny, Park, Frattali, & Braun, 2005;Zempleni et al, 1998) and emotional/affective prosody (George et al, 1996;Patel et al, 2018). In parallel with these associations, lesions in the right hemisphere have been reported to involve deficits in pragmatics; i.e., context-dependent use of language and nonverbal elements in communication (Lundgren & Brownell, 2016;Lundgren, Brownell, Cayer-Meade, Milione, & Kearns, 2011;Parola et al, 2016), and emotional prosody (Dara, Bang, Gottesman, & Hillis, 2014;Ross & Mesulam, 1979;Ross & Monnot, 2008;Stockbridge et al, 2021).…”
Section: Coactivation Patterns Of Left-hemispheric Roismentioning
confidence: 99%
“…These items predominantly address mobility, loneliness, mood changes, activities of daily living, and participation in social and medical activities. Individuals with RH stroke also did not consistently receive items 1–3, 15, 17–19, 21–50, but two additional inventory items were included in these administrations: (1) “had others say he/she is monotone or that he/she can't fully express emotions to others” and (2) “cared that his/her voice is monotone or that he/she can't fully express emotions to others.” These items were included to reflect the prevalence of aprosodia ( 33 ) in RH stroke. The 50-item and RH SPQ are included in Supplementary materials .…”
Section: Methodsmentioning
confidence: 99%